2011
DOI: 10.1111/j.1365-2141.2011.08721.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired immune function in children with Fanconi anaemia

Abstract: Summary Fanconi anaemia is an autosomal recessive or X-linked disease characterized by progressive bone marrow failure, variable congenital abnormalities and a predisposition to malignancy. Reports of immune function in this population are limited, and include only specific areas of immune performance, showing variable defects. We report a cross-sectional immunological assessment in 10 children with FA. Absolute numbers of B cells and natural killer (NK) cells were reduced compared to controls (P = 0·048 and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
50
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 28 publications
8
50
0
Order By: Relevance
“…This particular B-cell phenotype, not expected in children but in advanced age, may be due to a premature senescence affecting B cells in FA children (Myers et al , 2011 ).…”
Section: Prooxidant State In Fa: Evidence From Cellular and In Vivo Smentioning
confidence: 84%
“…This particular B-cell phenotype, not expected in children but in advanced age, may be due to a premature senescence affecting B cells in FA children (Myers et al , 2011 ).…”
Section: Prooxidant State In Fa: Evidence From Cellular and In Vivo Smentioning
confidence: 84%
“…Fanconi Anaemia is autosomal recessive or X-linked congenital disease, characterized by progressive bone marrow failure, developmental defects, predisposition to malignancy and different alterations in immunologic function (impairment of T-cell function, NK and macrophage function [7,8]. Haematopoietic stem cell transplantation may be associated with several complications, including neurologic, which may be secondary to the treatment toxicity, prolonged immunosuppression or an underlying disease.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the first systematic and broad evaluation of immune function in FA patients, Myers and colleagues reported that absolute numbers of B cells and natural killer (NK) cells were reduced in FA patients compared with controls, whereas the absolute number of T cells was within normal range, although cytotoxic T-cell function was reduced. 17 Perforin and granzyme content of NK-cells was reduced along with NK-cell cytotoxicity (P , .001). Antigen proliferation in response to tetanus was also decreased whereas responses to candida and phytohemagglutinin were preserved.…”
Section: Introductionmentioning
confidence: 96%
“…Loss of FA functions causes excessive apoptosis of hematopoietic stem and progenitor cells (HSC/P) leading to BMF in the early stage of FA. [13][14][15][16][17] As the disease progresses, apoptosis as well as genomic instability impose a selective pressure on FA HSC/P cells. The loss of stem cell fitness in FA HSC/P cells permits the emergence of resistant clones, which could be transformed to leukemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation